Preventive role of genistein in an experimental non-alcoholic steatohepatitis model - Yalniz, Mehmet; Bahcecioglu, Ibrahim Halil; Kuzu, Nalan; Poyrazoglu, Orhan Kursat; Bulmus, Ozgur; Celebi, Selman; Şahin, Kazım (Wiley, 2007)
Background and Aim: The aim of the present study was to evaluate the preventive role of genistein, a phytoestrogen with a wide variety of pharmacological effects, in an experimental non-alcoholic steatohepatitis (NASH) model. Methods: Thirty-six Sprague-Dawley rats were divided into three groups. Group 1 (control) received only a standard rat diet, group 2 (placebo) was given a high fat diet (HFD) plus 0.5 mL/day saline subcutaneously, and group 3 (genistein group) a HFD plus subcutaneous genistein injection at dose of 0.2 mg/kg/day for 6 weeks. All rats were killed after 6 weeks. Serum aminotransferases, tumor necrosis factor (TNF)-alpha, transforming growth factor (TGF)-beta, and plasma and liver malondialdehyde (MDA) levels were measured. Additionally, steatosis, ballooning degeneration and inflammation of the liver were examined histopathologically. Results: Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (P < 0.001 for each), plasma and liver tissue MDA and plasma TNF-alpha levels (P < 0.001, < 0.001, < 0.01, respectively) were found to be higher in the placebo group than in the control group. TGF-beta levels, however, were comparable in the placebo and control groups (P > 0.05). Histopathologically, steatosis, inflammatory cells per mm(2) and ballooning degeneration were significantly higher in the placebo group than in the control group (P < 0.001 for each). Nevertheless, AST and ALT (P < 0.05 for each), plasma and liver tissue MDA (P < 0.05 for each) and plasma TNF-alpha levels (P < 0.001) were significantly decreased in the genistein group compared to the placebo group. Histopathologically, steatosis (P < 0.05), inflammatory cells per mm(2) and ballooning degeneration (P < 0.01 for each) in the genistein group were also significantly lower than in the placebo group. Conclusions: Genistein, a strong antioxidant agent, significantly decreased the plasma TNF-alpha level and remarkably prevented the emergence of NASH by improving the biochemical and histopathological abnormalities via attenuating oxidative stress.
Keywords: genistein; high fat diet; isoflavones; non-alcoholic steatohepatitis; oxidative stress